2019
DOI: 10.3390/cancers11111765
|View full text |Cite
|
Sign up to set email alerts
|

PTEN in Colorectal Cancer: Shedding Light on Its Role as Predictor and Target

Abstract: Molecular assessment of colorectal cancer (CRC) is receiving growing attention, beyond RAS and BRAF, because of its influence on prognosis and prediction in cancer treatment. PTEN (phosphatase and tensin homologue), a tumor suppressor, regulating cell division and apoptosis, has been explored, and significant evidence suggests a role in cetuximab and panitumumab resistance linked to the epidermal growth factor receptor (EGFR) signal transduction pathway. Factors influencing PTEN activity should be analyzed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 79 publications
2
51
0
Order By: Relevance
“…40 PTEN participates in the regulation of cell division, proliferation, apoptosis, migration, adhesion to surrounding tissues, and neovascularization. 41 Increasing evidence indicates that PTEN expression is associated with the prognosis and drug response of several tumors, such as prostate cancer, breast cancer, and endometrial carcinoma. 42 Our results suggest that PTEN expression may be a prognostic and predictive biomarker for chordomas; nevertheless, we also noted that there was no significant correlation between copy number loss of PTEN and clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…40 PTEN participates in the regulation of cell division, proliferation, apoptosis, migration, adhesion to surrounding tissues, and neovascularization. 41 Increasing evidence indicates that PTEN expression is associated with the prognosis and drug response of several tumors, such as prostate cancer, breast cancer, and endometrial carcinoma. 42 Our results suggest that PTEN expression may be a prognostic and predictive biomarker for chordomas; nevertheless, we also noted that there was no significant correlation between copy number loss of PTEN and clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic and prognostic molecular biomarkers have revolutionized clinical strategies for the management of patients with cancer. While the majority of previous studies have primarily focused on genetic and expression markers of protein-coding genes (38)(39)(40), only a few studies have investigated the potential roles of miRNA as biomarkers for clinical assessments of different types of human cancer (41)(42)(43). A number of studies have performed differential expression analyses of miRNAs in several types of cancer to investigate the role of miRNAs as clinical biomarkers and identified some miRNAs whose aberrant expression levels are associated with pathological and clinical phenotypes of patients with cancer (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Since expression of PTEN undergoes downregulation in cancer cells, it has attracted much attention in the field of cancer therapy [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. PTEN was first discovered in 1997 when mutations were investigated at 10q23 locus in chromosome 10, and it was found that PTEN is an onco-suppressor gene [ 24 ].…”
Section: Pten Signaling: An Overviewmentioning
confidence: 99%